2014
DOI: 10.1111/mve.12089
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide susceptibility of Anopheles coluzzii and Anopheles gambiae mosquitoes in Ibadan, Southwest Nigeria

Abstract: The emergence of insecticide resistance in Anopheles mosquitoes has great implications for malaria control in Nigeria. This study aimed to determine the dynamics of insecticide susceptibility levels and frequency of knockdown resistance (kdr) mutations (L1014F) in wild Anopheles coluzzii Coetzee & Wilkerson sp. n. and An. gambiae Giles ( (Diptera: Culicidae) from Ojoo and Bodija areas of Ibadan, South-West, Nigeria. Insecticide susceptibility to pyrethroids, organophosphates, carbamates and organochlorines was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
40
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 30 publications
(51 reference statements)
6
40
2
Order By: Relevance
“…In addition, this study found a hybrid form of A. gambiaes.s./A.coluzzii, which agrees with the findings from two recent studies [22]. The findings from our study and the previous reports showed that the hybridization of A. gambiaes.s./A.coluzzii is still rare with these two studies [21][22] reporting its occurrence in Nigeria at a low prevalence that ranges between 0.5% -0.8 %. Although, the epidemiological implication of the hybrid form to malaria control is still unclear, it should be a cause for concern because of the possible transference of "knock down resistant gene" (kdr gene) from A. gambiae to A.coluzzii [32,[36][37].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, this study found a hybrid form of A. gambiaes.s./A.coluzzii, which agrees with the findings from two recent studies [22]. The findings from our study and the previous reports showed that the hybridization of A. gambiaes.s./A.coluzzii is still rare with these two studies [21][22] reporting its occurrence in Nigeria at a low prevalence that ranges between 0.5% -0.8 %. Although, the epidemiological implication of the hybrid form to malaria control is still unclear, it should be a cause for concern because of the possible transference of "knock down resistant gene" (kdr gene) from A. gambiae to A.coluzzii [32,[36][37].…”
Section: Discussionsupporting
confidence: 93%
“…It is believed that small collections of water from rainfall and human activities will encourage A. gambiaes.s. to breed, in addition to the availability of blood meals from humans [6,21,38]. This was evident in the distribution of A. gambiae s.s in CRNP at 40% compared to 4% caught at Drill Ranch and none from Rhoko forest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this high frequency of L119F in this location is probably the reason why a lack of correlation was observed when comparing resistant and susceptible samples as observed regularly for kdr mutations such as L1014F in An. gambiae in situation when the 1014F resistant allele is nearly fixed [55]. The L119F-GSTe2 mutation has also been detected in other DDT resistant populations such as Ghana (44.2%) and Burkina-Faso (25%) in West Africa, and Cameroon (48.2%) in Central Africa [20, 23] as well as Uganda (20.4%) and Kenya (7.8%) in East Africa [12].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms responsible for resistance to insecticides used in mosquito control has also been identified and are of two main types namely; those mediated by changes at the target site of the insecticide (e.g. kdr mutations) and those caused by increase in the rate of insecticide metabolism resulting in increased metabolic detoxification [9,18]. Resistance to multiple insecticides (pyrethroids and organophosphates) has been reported in Ae.…”
Section: Introductionmentioning
confidence: 99%